Experiment on Cognitive Load of Gesture Interaction Based on Semiotics. Issue 1 (February 2020) - Sun, Wei; Jin, Yudi; Wang, JinLong; Yang, Hanbing
Abstract: Objective: To explore the amount of information contained in gesture symbols and its relationship with cognitive load, and to provide theoretical guidance for gesture interaction design based on semiotics. Methods: Firstly, a user-defined method was combined with oral analysis to collect gestures and establish a corresponding semantic knowledge base. Based on the knowledge base, the icon algebra theory is used to redesign the gesture symbols. Then through experiments combined with the NASA-TLX scale to measure the user's cognitive load, and through data analysis to explore the relationship between the amount of information contained in the gesture symbol and it. Conclusion: The amount of information contained in gesture symbols has a significant correlation with the user's cognitive load and response time. As the amount of gesture symbol information increases, the user's cognitive load and response time also increase accordingly. Based on this, a regression equation of user cognitive load and information amount of gesture symbols is established, which provides theoretical support for the design of gesture symbols based on semiotics.